Relevancia del juego y actividades recreativas en aulas hospitalarias - Mendoza Carrasco, Mariella Victoria (2019)
The importance of play as a learning tool must be considered in the educational and learning process of the student-patients who are hospitalized in health centers. Hospital Teaching is not widely used in our country, nor do we have Hospital Teaching Programs established by the Government. However, there are Agencies of Non-Governmental Organizations engaged in providing education and recreation for children and adolescents suffering from illness and who are hospitalized. For this reason, Hospital Teaching Programs provide education and use play as a learning and recreational tool to enhance the development of social and soft skills.